1996
DOI: 10.1111/j.1439-0507.1996.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood groups in relation to the infection rate of dermatophytosis

Abstract: The role of ABO blood groups in the carriage rate of dermatophytosis was studied. Blood grouping was done for 108 culture-proven dermatophytosis patients. Forty-nine patients belonged to blood group A, 54 to blood group O, three to blood group B and two to blood group AB. The incidence of dermatophytosis was found to be high in patients of blood group O and A. However, chronicity of the disease was more frequent in those in blood group A. The control group consisted of 100 healthy subjects. Sixteen out of 29 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…The cross reactivity between the fungal cell wall protein and the isoantign of ABO blood groups is presumed to be the cause for the selective susceptibility of certain blood group subjects to fungal diseases. [28]…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…The cross reactivity between the fungal cell wall protein and the isoantign of ABO blood groups is presumed to be the cause for the selective susceptibility of certain blood group subjects to fungal diseases. [28]…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…9 Grupos sanguíneos são antígenos de superfície celular expressos segundo padrões de herança bem determinados e estão associados à incidência ou ao prognóstico de diversas doenças, como carcinoma gástrico, tumor pulmonar de pequenas células, carcinoma de esôfago, susceptibilidade a dermatofitoses, líquen plano, dermatite seborreica, lúpus eritematoso sistêmico, câncer de mama, entre outras. [9][10][11][12][13][14] Há mais de 30 proteínas e açúcares reconhecidos como marcadores de grupos sanguíneos, entretanto os mais antigênicos compreendem aqueles pertencentes ao sistema ABO e Rh(D), segregados independentemente em genes situados nos cromossomos 9q34 e 1p36. [13][14][15][16] Os autores pretendem estudar a expressão dos grupos sanguíneos (ABO e Rh) em pacientes portadores de LECD.…”
Section: Introductionunclassified
“…12 But the study results of Neering et al and from the study done in our hospital by Selvi et al, no significant association with specific blood group and increased incidence of fungal infection has been proved. 13,14 The blood group distribution in our study showed 37.3% of patients belonging to blood group O +ve, 32% patients belonging to B+ve group, 21.3% patients belonging to A +ve and rest 9.4% to other groups.…”
Section: Mentagrophytesmentioning
confidence: 68%